Enhancement of saquinavir absorption and accumulation through the formation of solid drug nanoparticles - Gabriel Kigen; Geoffrey Edwards (BMC, 2018)
Abstract Background Nanotechnology is now considered a promising drug delivery method for orally administered hydrophobic drugs to their sites of action. The effect of nanodispersion on cellular transport and accumulation of saquinavir (SQV) was investigated. Methods The transport of five solid drug nanoparticle (SDN) SQV formulations along Caco-2 cell monolayers (CCM) was compared to that of standard SQV. The SDNs were prepared using SQV mesylate (20%), Pluronic F127 (10%) plus five other excipients (HPMC, PVP, PVA, Lecithin S75 and Span 80) in different proportions. Cellular accumulation in CEM parental and CEMVBL (P-gp overexpressing) cells was conducted to ascertain the effect of nanodispersion on P-gp mediated efflux of SQV. All SDN formulations were dissolved in water, whereas SQV in DMSO to improve solubility. Quantification was via HPLC. Results From transport results, an SDN sample composed of SQV mesylate/Pluronic F127 plus HPMC (70%) and had a 24% increase in apparent absorption compared to standard SQV, largely driven by a 38% reduction in basolateral to apical permeation. Additionally, the formulation and two others (SQV mesylate/Pluronic F127 alone; and + HPMC (65%)/Lecithin [5%]) accumulated more significantly in CEM cells, suggesting enhanced delivery to these cells. Moreover, accumulation and transport of the three SDNs compared well to that of SQV despite being dissolved in water, suggestive of improved dissolution. The inclusion of PVA resulted in increased efflux. Conclusion The use of HPMC and Pluronic F127 produced SQV SDNs with improved permeation in Caco-2 cells and improved accumulation in CEM cells, but negative effects with PVA.